Naringenin Produces Neuroprotection Against LPS-Induced Dopamine Neurotoxicity via the Inhibition of Microglial NLRP3 Inflammasome Activation - Chen, Ce; Wei, Yi-Zheng; He, Xue-Mei; Li, Dai-Di; Wang, Guo-Qing; Li, Jing-Jie; Zhang, Feng (Frontiers in Immunology, 2019)
Parkinson’s disease (PD) is the second most prevalent central nervous system degenerative disease and characterized by slow and progressive loss of dopamine (DA) neurons in the midbrain substantia nigra. Microglia-mediated neuroinflammation has been considered as the major central event in the process of DA neuronal loss. Thus, inhibition of neuroinflammation could possess a more viable strategy for PD treatment. Naringenin (NAR), a natural flavanoid contained in citrus fruit and grapefruits, possesses amounts of pharmacological activities, such as anti-oxidative, anti-inflammatory and anti-tumor properties. Recent studies indicated that NAR produced neuroprotection against several neurological disorders. However, the mechanisms underlying NAR-generated neuroprotection are not fully illuminated. In the present study, rat nigral stereotaxic injection of lipopolysaccharide (LPS)-induced DA neuronal loss was performed to investigate NAR-mediated neuroprotection. In addition, BV-2 and MN9D cell lines were applied to explore the underlying mechanisms. Results indicated that NAR protected DA neurons against LPS-induced neurotoxicity. Also, NAR suppressed microglial nod-like receptor protein 3 (NLRP3) inflammasome signaling activation and the subsequent pro-inflammatory factors release. In addition, NAR-mediated DA neuroprotection was dependent on the inhibition of microglial NLRP3 inflammasome activation, as evidenced by the observations that NAR-reduced pro-inflammatory factors production and further NAR-exerted DA neuroprotection against LPS-induced neuronal damage was not discerned after microglial NLRP3 siRNA treatment. Together, this study demonstrated that NAR targeted microglial NLRP3 inflammasome to protect DA neurons against LPS-induced neurotoxicity. These findings suggest NAR might hold a promising therapeutic potential for PD.